Peningkatan Keterampilan Menulis Narasi dengan Model Cooperative Integrated Reading and Composition pada Siswa Kelas IV MI Al-Mukhlisin Kota Jambi - Windha Afriyanti Harahap; Sean Popo Hardi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This research was motivated by the low narrative essay writing skills of class IV students at Madrasah Ibtidaiyah Al-Mukhlisin, Jambi City. The aim of this research is to improve the process and skills of writing students' narrative essays using the cooperative integrated reading and composition model in the Madrasah Ibtidaiyah Al-Mukhlisin class in Jambi City. This research is a classroom action research consisting of two cycles. The subjects of this research were students from the Madrasah Ibtidaiyah Al-Mukhlisin class in Jambi City. The research results showed that the average teacher observation score in cycle I was 79 and in cycle II it increased to 89.55 in the